2022
DOI: 10.1002/adfm.202211983
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Stimuli‐Responsive Smart Membranes for Nanofiltration

Abstract: Nanofiltration membrane plays an increasingly important role in many industrial applications, such as water treatment and resource recovery. The performance of the smart nanofiltration membrane is largely controlled by pore size, the Donnan effect, and surface wettability, which are determined by the function of stimuli‐responsive components. Smart membranes, which contain stimuli‐responsive components, are capable of changing their physical and chemical properties in response to changes in the environment so … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 265 publications
0
18
0
Order By: Relevance
“…[17] The membrane wettability will change depending on the pH of the solution, which popularly results from the pH-induced reversible protonation or deprotonation of acid-base groups on the surface. [18] For example, Cheng et al [19] reported the pH-responsive membranes with excellent superwettability. Due to the protonation of acid-base groups, they could realize the reversible and controllable surface wettability in response to the surrounding solution pH.…”
Section: Introductionmentioning
confidence: 99%
“…[17] The membrane wettability will change depending on the pH of the solution, which popularly results from the pH-induced reversible protonation or deprotonation of acid-base groups on the surface. [18] For example, Cheng et al [19] reported the pH-responsive membranes with excellent superwettability. Due to the protonation of acid-base groups, they could realize the reversible and controllable surface wettability in response to the surrounding solution pH.…”
Section: Introductionmentioning
confidence: 99%
“…11 In recent years, membrane technology has garnered increasing attention for extracting lithium from lithium-containing solutions, like seawater and brine lakes, owing to its advantages of low cost, environmental protection, and nonphase transition. 12,13 By offering a more cost-effective and efficient alternative to traditional technologies, membrane technology opens new possibilities for lithium extraction processes. 13,14 The development of novel membrane materials is of paramount importance for the advancement and application of membrane technology.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional commercial lithium extraction techniques, including calcination impregnation, liquid phase extraction, chemical precipitation, and adsorption, encounter issues such as secondary pollution, high cost, low recovery rate, and poor selectivity . In recent years, membrane technology has garnered increasing attention for extracting lithium from lithium-containing solutions, like seawater and brine lakes, owing to its advantages of low cost, environmental protection, and nonphase transition. , By offering a more cost-effective and efficient alternative to traditional technologies, membrane technology opens new possibilities for lithium extraction processes. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12][13] Leveraging the integration of diverse stimuli-responsive materials, the intelligent 2D material membranes exhibit an attractive ability to autonomously modulate their permeability and selectivity by dynamically adapting their channel properties in response to external cues-ranging from pH and temperature to light, electric/magnetic fields, and specific ions/molecules. [14][15][16][17] Among these triggers, pH stands as a particularly pivotal parameter in wastewater treatment applications. Notably, a repertoire of pH-sensitive polyelectrolytes, including polyamine (PA), polyacrylic acid (PAA), polyethylenimine (PEI), and poly(4-vinylpyridine) (P4VP), has been ingeniously integrated into 2D material membranes via grafting, coating, or attachment methodologies.…”
Section: Introductionmentioning
confidence: 99%